14.1k views
0 votes
I need help solving this ACT Prep Guide 21’-22’ problem in calculus -Rose

I need help solving this ACT Prep Guide 21’-22’ problem in calculus -Rose-example-1
User Chris Bier
by
4.5k points

1 Answer

1 vote

x²(x + 3)⁴(x - 1) = 0

For this expression to be equal to zero, it means that at least one of the factors is equal to zero. Thus:

x² = 0

x = √0

x = 0

(x + 3)⁴ = 0

x + 3 = ∜0

x + 3 = 0

x = -3

x - 1 = 0

x = 1

The polynomial has three roots.

User Omid Shagiwal
by
4.7k points